2015
DOI: 10.1038/srep14178
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous TiO2 Yolk-Shell Microspheres for Dye-sensitized Solar Cells with a High Efficiency Exceeding 11%

Abstract: Yolk-shell TiO2 microspheres were synthesized via a one-pot template-free solvothermal method building on the aldol condensation reaction of acetylacetone. This unique structure shows superior light scattering ability resulting in power conversion efficiency as high as 11%. This work provided a new synthesis system for TiO2 microspheres from solid to hollow and a novel material platform for high performance solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…The power conversion efficiency (PCE) of perovskite device has undergone a rapid development from 3.8% to 22.1% since the first attempt to introduce organic-inorganic hybrid perovskite materials as the light absorber [1][2][3][4][5][6][7][8][9][10]. Such rapid increase in performance can be ascribed to its excellent properties, such as, ambipolar charge transport, high carrier mobility, long carrier diffusion, and large absorption coefficient [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The power conversion efficiency (PCE) of perovskite device has undergone a rapid development from 3.8% to 22.1% since the first attempt to introduce organic-inorganic hybrid perovskite materials as the light absorber [1][2][3][4][5][6][7][8][9][10]. Such rapid increase in performance can be ascribed to its excellent properties, such as, ambipolar charge transport, high carrier mobility, long carrier diffusion, and large absorption coefficient [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid organic-inorganic halide perovskites have been verified to be in possession of many excellent properties, such as long electron/hole diffusion length [3], remarkable sunlight absorption [4], easy and low-cost fabrication process [5], etc., which make them an ideal candidate for lots of applications in photodetectors [6], light-emitting devices [7], semiconductor lasers [8], and solar cells [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al reported a one-pot template-free solvothermal alcoholysis method for preparing yolk-shell TiO2 microspheres based on the aldol condensation and robinson cyclization reaction between acetylacetone and tetra-n-butyl titanate [72]. By controlling the reaction time, microspheres with adjustable morphology, size and tunable interior structure from solid to yolk-shell structure were obtained.…”
Section: Tio2 Micro-structurementioning
confidence: 97%
“…For example, the TiO2 yolk-shell microspheres encapsulated by the TiO2 film could be used as a scattering layer in dyesensitized solar cells (DSSCs) with enhanced cell efficiency compared to those of pure TiO2 films without any scattering layers [72]. The TiO2 yolk-shell microspheres were successfully applied as photoanode to construct DSSC.…”
Section: Photocatalysis For Energy Production and Storagementioning
confidence: 99%